TI_GERICHTE 52.2006.170 vom 6. Juli 2006 , Esclusione da parte della committente di un'impresa partecipante ad un pubblico concorso - TI Tribunale d'appello (2006)
Esclusione da parte della committente di un'impresa partecipante ad un pubblico concorso